USTANAWIANIE AMERYKAŃSKIEJ WŁADZY KOLONIALNEJ NA FILIPINACH - Lewicki, Zbigniew (Zeszyty Prawnicze, 2016)
Establishing American Colonial Government in the Philippines Summary The Philippines was the only American colony and its establishment caused a fierce debate in the United States on whether this complied with the principles of American civil society. It was decided that returning the archipelago to Spain or simply abandoning it was out of the question, and that the USA would retain its sovereignty over the islands while preparing the country for independence. This is in fact what happened. After the period of military struggle with the forces of Emilio Aguinaldo, Americans began what would today be described as a nation-building process. Its most important components were the health system and education, along with the training of administrative staff, who assumed more and more responsibility. This was in stark contrast with the behaviour of traditional colonial powers. While the process was somewhat slower than expected, and was interrupted by the outbreak of World War 2, the Philippines became independent soon after the war and the process of transition was conducted in an orderly fashion. The article, the first on the topic in Poland, analyses the successive phases in the building up of American colonial control of the Philippines and its subsequent withdrawal.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />